Il trattamento delle lesioni massive di cuffia con lo spaziatore biodegradabile sottoacromiale - Bortolato, S.; Zacchinato, G.; Micheloni, G.M.; Salmaso, G. (Lo Scalpello - Journal, 2019)
TREATMENT OF MASSIVE ROTATOR CUFF TEARS WITH SUBACROMIAL BIODEGRADABLE SPACERS The treatment of massive rotator cuff tears remains a challenge for orthopaedic surgeons. There are several arthroscopic possibilities in the absence of glenohumeral arthrosis: debridement with or without tenotomy of the long head of the biceps, partial cuff repair, use of synthetic patches and insertion of a biodegradable spacer. The aim of our study was to provide a clinical and subjective analysis of patients treated in our centre using the InSpace™ balloon. The spacer is positioned in the subacromial space. This device should reduce subacromial friction so as to lead to pain reduction and improvement in the range of motion. We analysed 27 patients (15 men and 12 women) treated with this technique between December 2014 and December 2018 in our Operative Unit. Mean age was 65 years (49–71) and average follow-up time was 24.4 months. All patients had massive rotator cuff lesions associated with subacromial bursitis. In 16 cases this lesion was associated with biceps tendinitis and, in 4 patients, with partial lesion of the subscapularis tendon. Patients underwent bursectomy and tenotomy of the long head of the biceps brachii. In 6 cases the cuff was partially reconstructed using 1 or 2 anchors and side-to-side sutures. The average Constant Score rose from 11.33/100 to 78.00. In 4 cases the Constant Score was unsatisfactory, while in the remaining patients it exceeded 85 points. The UCLA score increased from an average value of 1.33/10 points to 8.62, while the SST score rose from 2.33/12 to 10.54 points. The final result seems to be independent of severity of the initial injury, time elapsed and cuff reconstruction. Proper use of the spacer seems to be effective against pain and ROM restoration. Our goal is to continue the follow-up in these patients and to evaluate the advantages of this device in a larger sample.